Double grudge donuts - Bolton, Ginger (Bolton, Ginger. Deputy Donut mystery., 2024)
Deputy Donut Café owner Emily Westhill and her cat investigate a contest-winning bagpiper's death when one of their coffee mugs turns up at the crime scene.